Effekt av spädningsvätska på spermiemembranintegritet analyserad med NucleoCounter SP-100 - Junttila, Laura (2009)
This study is a part of a larger project where the aim has been to evaluate different methods to assure the quality in stallion semen, due to the fact that some stallions in horse breeding have poor semen quality. The increased use of transport semen requires new methods to ensure good semen quality.